Kwestie etyczne w prawie giełdowym okresu zaborów i pierwszych lat niepodległości Polski (do 1921 r.) - Marks, Bogusław Piotr (Annales. Etyka w Życiu Gospodarczym, 2010)
The object of the article are the questions concerning the „ethical aspects” of functioning of stock exchange law during partitions of Poland and in the first years of independent Poland. The analysis covers the period from 1817 (when in Warsaw the first official stock exchange on Polish territory was created) to 1921 when the first in independent Poland Act about the Organization of Stock Exchanges was passed. In the 19th century, several stock exchanges were created on Polish territory, from which the most essential were those in: Warsaw, Lvov and Lodz. The stock exchange was (and still is) regarded as one of the key institutions of market economy. Already, even on this account, the stock exchange law constituted the essential reference to economic law. On its basis the important institutions functioned, not only in the area of economy. In this article, the basic records of laws and exchange charters were traced, as well as different – essential for stock exchanges – documents (for instance, ministerial instructions), which set the principles of functioning of those institutions. The principles were considered from ethical norms’ point of view, which established ethics of economic life of that time. I have especially focused my attention on the principles of functioning of stock exchanges, which related to: the main stock organs, members of exchanges, as well as the so-called clientele. The stock exchange law also related to realities of that time, where-for different reasons – common cases of disobedience of the law occured. It should be stressed here, that stock exchange law was shaped on basis of economic legislation of the partitioners and that it was subject to changes along with political, economic and social transformations, which took place on Polish territory in the discussed period.